Antiarrhythmic drug treatment: need for continuous vigilance. Issue 1 (January 1992) - Wellens, H J; Smeets, J L; Vos, M; Gorgels, A P
Abstract : Any physician treating cardiac arrhythmias should be aware of a possible worsening of the arrhythmia (so-called arrhythmogenesis) after the start of antiarrhythmic drug treatment. To facilitate the recognition of that complication the type and possible mechanisms of arrhythmogenesis are reviewed. Recognition also requires an understanding of (a) the time of appearance of arrhythmogenic effects after different drugs, (b) the value of non-invasive and invasive tests, and (c) the profile of the patient most likely to develop this problem. Guidelines are given to reduce the incidence of the arrhythmogenic effects of antiarrhythmic drugs and a plea is made that the physician should be always on the alert for this complication.